Flawed convictions : "Shaken Baby Syndrome" and the inertia of injustice - Tuerkheimer, Deborah (New York : Oxford University Press, 2014)
This text surveys the scientific, cultural, and legal history of 'Shaken Baby Syndrome' from inception to formal dissolution. Deborah Tuerkheimer exposes extraordinary failings in the criminal justice system's treatment of what is, in essence, a medical diagnosis of murder.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on March 17, 2014).
Keywords: Child abuse -- Law and legislation -- United States; Shaken baby syndrome -- United States